Predictability of foreign aid and economic growth in Ethiopia - Tewodros Girma; Solomon Tilahun (Cogent Economics & Finance)
Foreign aid is one source of physical capital accumulation in Ethiopia. It is also a main media of government revenue in meeting increasing trends of government expenditure. To investigate the impact of foreign aid flow on economic growth, various empirical studies were conducted, but they came up with mixed result. This leads to raise question of why impact of aid on economic growth in Ethiopia continues to be paradoxical in its findings. To assess the effectiveness of foreign aid in Ethiopia; this study sets predictability of foreign aid and economic growth in Ethiopia as a general objective. Specifically, the study sought to examine the contribution of foreign aid and the macroeconomic policy environment to economic growth in the country. In order to meet the aforementioned objective, the study employed an autoregressive distributed lag (ARDL) approach over the period 1985–2019. The empirical finding shows that foreign aid has a positive role in economic growth in the long run but its short run effect is found to be insignificant. Again, this finding also reveals that both in the short run and long run the predictability of foreign aid has a positive effect both on economic growth. Macroeconomic policy index also has a positive effect in the long run, but its short run effect become negative. Based on the listed empirical finding, the study came up with policy recommendation; the government should allocate the external assistance on the successful development projects rather than simply on consumption. Furthermore, for the persistent and predictable flow of foreign aid overtime, joint mechanism of transparency has to be developed between Ethiopian government and donor communities.